2015
DOI: 10.1007/s11356-015-5921-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and renal toxicity after subacute exposure to decabrominated diphenyl ether in Wistar rats

Abstract: Fully brominated diphenyl ether (BDE-209) is a flame retardant widely used in plastics and textiles. Because of its high persistence, humans are exposed to it continuously, mainly via dust ingestion. We investigated effects of BDE-209 on renal function and oxidative stress development in the kidney after subacute exposure in rats. Five groups of animals were given by oral gavage 31.25-500 mg BDE-209/kg b.w./day for 28 days, and relative kidney weight, serum urea and creatinine, and oxidative stress parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
10
0
3
Order By: Relevance
“…Another important issue relating to thyroid-disrupting substances and ED substances is the fact that humans are more often exposed to multiple disrupting substances simultaneously and these substances can exert additive or even synergistic effects [ 53 ]. Particular attention was given to mixtures consisting of metals and persistent organic pollutants, especially those which are highly toxic compounds and already established disruptors of thyroid function such as polychlorinated biphenyls (PCB) [ 54 , 55 , 56 ] and polybrominated diphenyl ethers [ 57 , 58 , 59 ]. Study on mixtures of Cd and PCB [ 52 ] revealed possible synergistic effects of Cd and PCBs on T3 and T4 levels after 28 days of oral administration of a Cd-PCB mixture in Wistar rats.…”
Section: Cadmium Effects On Thyroid Functionmentioning
confidence: 99%
“…Another important issue relating to thyroid-disrupting substances and ED substances is the fact that humans are more often exposed to multiple disrupting substances simultaneously and these substances can exert additive or even synergistic effects [ 53 ]. Particular attention was given to mixtures consisting of metals and persistent organic pollutants, especially those which are highly toxic compounds and already established disruptors of thyroid function such as polychlorinated biphenyls (PCB) [ 54 , 55 , 56 ] and polybrominated diphenyl ethers [ 57 , 58 , 59 ]. Study on mixtures of Cd and PCB [ 52 ] revealed possible synergistic effects of Cd and PCBs on T3 and T4 levels after 28 days of oral administration of a Cd-PCB mixture in Wistar rats.…”
Section: Cadmium Effects On Thyroid Functionmentioning
confidence: 99%
“…72 Similarly, polybrominated diphenyl ethers have shown to affect kidney function by inducing oxidative stress. 73 The organophosphate FR, tris (2-chloroethyl) phosphate, has also exhibited potential in inducing focal hyperplasia of the renal tube epithelium and therefore inducing renal tube adenomas in rats. 74 Finally, DOPO was found to harbour potential effects on cell fate determination and embryonic development, specifically kidney development and formation.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity and environmental behavior of BDE-209 have been studied less than those of low-brominated congeners. BDE-209 is known to exert toxic effects on the endocrine, nervous, cardiac, and reproductive systems in rats, zebrafish, and other terrestrial or freshwater vertebrates (He et al, 2011;Milovanovic et al, 2015;Zhu et al, 2016;Han et al, 2017), while less attention has been paid to the impacts of BDE-209 on marine organisms. The toxic effect of PBDEs is yet to be fully explored in the marine organisms.…”
Section: Introductionmentioning
confidence: 99%